Variation of Sandalwood (Santalum album Linn.) Based on Morphology of Leaves and Flowers at Petir Village, Rongkop, Gunungkidul - Ridla Arifriana; Sapto Indrioko; Atus Syahbudin (Jurnal Ilmu Kehutanan)
Sandalwood (Santalum album Linn.) is one of the flora that are commonly used as rehabilitation species, known as a plant that can grow in a lack of nutrient soil, and has a high economic value of santalol oil. This plant is indigenous in East Nusa Tenggara but it has a natural regenaration in some areas of Gunungkidul Yogyakarta, including in Petir Village, Rongkop, Gunungkidul. Morphological variation of Sandalwood in this area was relatively high. This research aimed to describe and classify sandalwood variations that exist in the research site based on the morphological characters. The materials used in this study were (1) sandalwood as the target species (including generative and vegetative organs) with purposive sampling and (2) Ximenia americana as the outgroup species. Data were analyzed using description and phylogeny analysis using maximum parsimony method with morphological markers. Morphological characters of Sandalwoods were varied in size and leave shapes, flowers perigonium, lobes shapes, appendices shapes, stem color, shapes and fruit size. There were two characters that have not been described in the previous sources in Indonesia, form of leaves (oblong and oval) and orange color of perigonium. Phylogeny results showed that a small leaf sandalwood character was closer to the outgroup character. Diagnostic characters explicitly classified small leaf size and leaf size large. Size of small leaf was from 2.8 -7.7 cm to 1.1-2.2 cm and from 7.9-10 cm to 3.1-4 cm for large leaf. Leaf form and colour of flower variation was found in each group of leaf size.